Ефірна олія Nepeta cataria як основа виробництва натуральних ароматизаторів для харчової промисловості - Фролова, Н. Е.; Карпутіна, М. В.; Березка, Тетяна Олександрівна (НТУ "ХПІ", 2015)
Приведено результати дослідження умов спрямованого фракціонування ефірної олії Nepeta cataria. Встановлено параметри процесу для кожної фракції – залишковий тиск, температурні режими, флегмове число. Отримано чотири фракції (ароматизатора) різної тональності аромату. Застосовування фізичних процесів перероблення ефірної олії не руйнує природні структурні зв'язки, зберігає натуральність, біологічну здатність. Комбінування фракцій із залученням комп'ютерних програм дозволяє поширити лінійку натуральних ароматизаторів з однієї ефірної олії для харчової промисловості.

The results of study of Nepeta cataria essential oil directed fractionation conditions were shown. The parameters of the process for each faction – the residual pressure, temperature, reflux ratio were estimated. Four fractions (flavor) of different tones of flavour were obtained. Parameters values of division for the binary systems of Nepeta cataria essential oil were calculated. Physical refining processes of the essential oil does not destroy the natural structural links, keeps naturalness, biological capacity. Combining of the fractions using the software tools extends the range of natural flavours obtained from one of essential oil for the food industry. New flavours on the basis of Nepeta cataria essential oil have not only the pleasant aroma concerted, but also a high saturation and improving stability. Shelf-life of such flavours at a room temperature is 24 months. The obtained flavours have social and production query, as it will promote the production of the high-quality food products on natural aromatic basis.
Essential oil Nepeta cataria as a basis for natural flavours production for the food industry
Keywords: ароматизатори натуральні; ефірна олія; харчові технології; фракціонування; комбінування; тональність; essential oil; fractionation; flavours; combining; tonality